STUDI PEMBERIAN IMUNISASI DASAR LENGKAP DI PUSKESMAS DITINJAU DARI KARAKTERISTIK IBU, SIKAP, DAN TINDAKANNYA - Zaim Anshari (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
A child's health care is the responsibility of parents that can do through many actions. It is one of the efforts that can do through giving a complete necessary immunization to his son. The purpose of this research is to look for the characteristics of sexual relations, attitudes and actions of mothers with the provision of necessary immunizations in infants. This research conducted at Public health in Simpang Limun with 41 people as a population. That amount as well as samples of this research. This study refers to the analytical studies, so it is concluded that the sample characteristics based on age, level of education, and type of work, in which the most age groups are between 26 to 32 years (41.5%), for the highest level of education is SMA (48.8%), and for the most types of work are not working (41.5%). The better the level of knowledge about immunization will improve the attitude (positive) shown on immunization to the child. The level of education of one does not affect immunization actions to their children. It is like the type of work that parents have on immunization administration.